Protofibrillar Amyloid Beta Modulation of Recombinant hCaV2.2 (N-Type) Voltage-Gated Channels - Eleni Kaisis; Laura J. Thei; Gary J. Stephens; Mark L. Dallas (MDPI AG, 2022)
Cav2.2 channels are key regulators of presynaptic Ca2+ influx and their dysfunction and/or aberrant regulation has been implicated in many disease states; however, the nature of their involvement in Alzheimer's disease (AD) is less clear. In this short communication, we show that recombinant hCav2.2/b1b/a2d1 channels are modulated by human synthetic AD-related protofibrillar amyloid beta Ab1-42 peptides. Structural studies revealed a time-dependent increase in protofibril length, with the majority of protofibrils less than 100 nm at 24 h, while at 48 h, the majority were longer than 100 nm. Cav2.2 modulation by Ab1-42 was different between a 'low' (100 nM) and 'high' (1 µM) concentration in terms of distinct effects on individual biophysical parameters. A concentration of 100 nM Ab1-42 caused no significant changes in the measured biophysical properties of Cav2.2 currents. In contrast, 1 µM Ab1-42 caused an inhibitory decrease in the current density (pA/pF) and maximum conductance (Gmax), and a depolarizing shift in the slope factor (k). These data highlight a differential modulation of Cav2.2 channels by the Ab1-42 peptide. Discrete changes in the presynaptic Ca2+ flux have been reported to occur at an early stage of AD; therefore, this study reveals a potential mechanistic link between amyloid accumulation and Cav2.2 channel modulation.